Sinergi Pemerintah, Lembaga Pendidikan, dan Masyarakat dalam Penguatan Moderasi Beragama di Indonesia - Helmi; Muhammad Zam Zami; Muhammad Azzurqani; Ilham Arifin; Fairuz Fatin (Yayasan Nanggroe Aceh Mulia, 2026)
Indonesia is a country with religious, cultural, and ethnic diversity that requires tolerance and harmony in social life. In facing various social challenges, religious moderation has become an important effort to maintain national unity and prevent intolerance and extremism. Strengthening religious moderation cannot be carried out by only one party, but requires synergy between the government, educational institutions, and society. This study aims to analyze the form of synergy among the government, educational institutions, and society in strengthening religious moderation in Indonesia and to identify factors influencing the effectiveness of its implementation. This research uses a library research method with a qualitative descriptive approach through collecting and analyzing various written sources, such as books, journals, scientific articles, and previous studies relevant to the research topic. The results show that the government plays an important role in formulating policies and programs related to religious moderation, educational institutions contribute to instilling tolerance and moderate attitudes in students, while society implements moderation values in daily social life. The study also finds that coordination and communication among various parties are still not optimal, causing the strengthening of religious moderation to be not fully implemented comprehensively and sustainably. Therefore, more integrated cooperation, effective communication, and active participation from all elements of society are needed to support the strengthening of religious moderation in Indonesia. This study contributes to expanding research on cross-sector synergy in supporting religious moderation and maintaining social harmony in Indonesian society.